Electric vehicle charging modeling and forecasting - Ainiwaerjiang, Subi (Nanyang Technological University, 2022)
The development of electric vehicles (EVs) has emerged as a critical component of the solution to the environmental and energy crises. When many electric vehicles are connected to the electrical grid, however, the distribution network's safety and stability will be jeopardized. The goal of this project is to create a Monte Carlo technique model for describing electric vehicle (EV)’s charging behavior and forecasting charging power requirements, as well as to incorporate elements like parking time into the model to increase prediction accuracy. The creation of such a model will be able to precisely estimate the EV load and effectively reduce grid pressure.